The Role of Environmental Law in Realizing Environmental Sovereignty to Ensure Social and Environmental Justice - Prasetyo, Mas Subagyo Eko (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to analyze the role of environmental law in realizing environmental sovereignty as an effort to ensure social and environmental justice. Environmental law is viewed not only as a normative instrument but also as a strategic means to regulate, protect, and sustainably manage natural resources. Using a normative-juridical approach with qualitative descriptive analysis, this study examines applicable regulations, environmental law principles, and their implementation in the context of ecosystem protection and the fulfillment of community rights. The results indicate that the implementation of environmental law in Indonesia has a strong legal basis through Article 28H and Article 33 paragraph (3) of the 1945 Constitution, as well as Law No. 32 of 2009 concerning Environmental Protection and Management. Environmental law plays a crucial role in realizing environmental sovereignty because it guarantees the community's right to a good and healthy environment and regulates the management of natural resources for the people's prosperity. However, in practice, various obstacles remain, such as conflicts between economic development and ecosystem protection, weak law enforcement, limited human resources, low public awareness, and regulatory weaknesses that often stop at the normative level. This indicates a gap between ideal regulations and their implementation in the field.